A Heterogeneous Agent Model of Asset Price with Three Time Delays - Matsumoto, Akio; Szidarovszky, Ferenc (Frontiers in Applied Mathematics and Statistics, 2016)
This paper considers a continuous-time heterogeneous agent model of a ...nancial market with one risky asset, two types of agents (i.e., the fundamentalists and the chartists), and three time delays. The chartist demand is determined through a nonlinear function of the di¤erence be- tween the current price and a weighted moving average of the delayed prices whereas the fundamentalist demand is governed by the di¤erence between the current price and the fundamental value. The asset price dy- namics is described by a nonlinear delay di¤erential equation. Two main results are analytically and numerically shown: (i) the delay destabilizes the market price and generates cyclic oscillations around the equilibrium; (ii) under multiple delays, stability loss and gain repeatedly occurs as a length of the delay increases.